Toxic Trails: Land Degradation Induced By Pollutants - Shadab Ali; Anuradha Singh; Amar Singh Kashyap (International Journal of Land, 2024)
Land degradation, driven by various pollutants, poses a significant threat to global ecosystems, agriculture, and human well-being. This review article explores the mechanisms through which pollutants, including heavy metals, pesticides, industrial chemicals, and urban waste, contribute to soil erosion, salinization, acidification, and loss of soil biodiversity. The article presents detailed case studies from regions such as China, India, Nigeria, the United States, Europe, Sub-Saharan Africa, and Australia, highlighting the diverse impacts of land degradation across different environmental and socio-economic contexts. Agroforestry, crop rotation, conservation tillage, and organic farming are examples of sustainable land management techniques that are included in the critical discussion of mitigation and remediation solutions. Pollution control measures, including regulatory frameworks, waste management, and best management practices in agriculture, are emphasized as essential steps in preventing further degradation. The article also reviews various remediation technologies, such as phytoremediation, bioremediation, soil washing, thermal desorption, and chemical stabilization, which are used to restore contaminated soils. Finally, the role of international and national policies, including the United Nations Convention to Combat Desertification (UNCCD), is examined in promoting sustainable land use and achieving land degradation neutrality. The paper emphasizes the significance of integrated strategies that incorporate community involvement, policy-making, and scientific research to successfully address the problems associated with pollution-related land degradation.
Keywords: Biodiversity; Climate; Degradation; Sustainability; deforestation; desertification; erosion; fertility; restoration; urbanization